Glutamic Acid Production by Lactic Acid Bacteria Isolated from Indonesian Fermented Food Salted Mustard Greens and Dangke Cheese - Indahsari, Silvana Nurulfauziyyah; Jannah, Siti Nur; Lunggani, Arina Tri (Perhimpunan Ahli Teknologi Pangan Indonesia bekerjasama dengan Departemen Ilmu dan Teknologi Pangan, IPB University Bogor, Indonesia, 2025)
Glutamic acid is an additive compound widely added to food to enhance the savory taste (umami). Lactic acid bacteria (LAB) are included in Generally Recognized as Safe (GRAS) and have the potential to produce various metabolite compounds, including glutamic acid, through fermentation. LAB can be isolated from salted mustard greens and dangke cheese. This study aimed to analyze the effect of LAB isolate types and fermentation time on the production of glutamic acid, glutamic acid profiling, and molecularly identify the LAB genus that produces the highest glutamic acid based on the 16S rRNA gene. The fermentation process of LAB was carried out using four selected isolates: D16, D15, S4, and S15, which were isolated from salted mustard greens and dangke cheese. Each isolate was incubated for five different incubation times: 0, 12, 24, 48, and 72 h. The identification of glutamic acid was carried out using the Thin Layer Chromatography (TLC) method, its quantification by spectrophotometry, and profiling by High-Performance Liquid Chroma-tography (HPLC). In addition, molecular identification of the highest-producing LAB isolate was conducted based on the 16S rRNA gene. The results showed that isolate S4 from salted mustard greens produced the highest glutamic acid after 48 h, with 670.05 mg/L and a total glutamic acid of 0.23% (w/w) based on HPLC results. Isolate S4 is known to be molecularly similar to the Pediococcus pentosaceus species. Local LAB isolates from salted mustard greens and dangke cheese can produce glutamic acid that can be used to enhance the taste of fermented foods.